2022
DOI: 10.1093/jamiaopen/ooac047
|View full text |Cite
|
Sign up to set email alerts
|

MyCap: a flexible and configurable platform for mobilizing the participant voice

Abstract: This paper provides a description of the MyCap data collection platform, utilization metrics, and vignettes associated with use from diverse research institutions. MyCap is a participant-facing mobile application for survey data collection and the automated administration of active tasks (activities performed by participants using mobile device sensors under semi-controlled conditions). Launched in 2018, MyCap is a no-code solution for research teams conducting longitudinal studies, integrates tightly with RED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…We chose a continuous measure of dosing error because no standardized, clinically meaningful definition of dosing error exists, and this approach best captures the full spectrum of possible dosing errors. Outcomes were collected using MyCap (Vanderbilt University), a Health Insurance Portability and Accountability Act–compliant, participant-facing mobile application for survey data collection and automated administration of study tasks, including transmission of high-resolution images . After enrollment, study staff assisted caregivers in downloading MyCap on their mobile devices and demonstrated how to complete the image upload and follow-up survey.…”
Section: Methodsmentioning
confidence: 99%
“…We chose a continuous measure of dosing error because no standardized, clinically meaningful definition of dosing error exists, and this approach best captures the full spectrum of possible dosing errors. Outcomes were collected using MyCap (Vanderbilt University), a Health Insurance Portability and Accountability Act–compliant, participant-facing mobile application for survey data collection and automated administration of study tasks, including transmission of high-resolution images . After enrollment, study staff assisted caregivers in downloading MyCap on their mobile devices and demonstrated how to complete the image upload and follow-up survey.…”
Section: Methodsmentioning
confidence: 99%
“…They will receive detailed instructions on using both devices correctly, including removing them when in contact with water and during contact sports. Participants will also install the MyCap app (Harris et al, 2022), which is used to fill in daily questionnaires and set alarms on their phones as reminders to complete the scheduled questionnaires on the app. Before leaving, participants will complete two questionnaires measuring circadian time and circadian preference (MCTQ and MEQ, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, only people based at or near (<60 km) the local hubs of each geographical location during the weekdays (Monday to Friday) of the experiment will be accepted for this study to have similar environmental conditions across participants at each measurement hub. All criteria mentioned above for inclusion and exclusion will be assessed by self-report through an online platform developed for this purpose (Research Electronic Data Capture, REDCap; (Harris et al, 2009(Harris et al, , 2019(Harris et al, , 2022). The eligibility criteria used here can be modified for studies in which the goal is to assess a different population.…”
Section: Sample Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…Evaluation is ongoing, and metrics have been published for some innovations, while others are still being tested [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. A TIN Work Group established to develop metrics agreed upon 10 priority metrics and data elements to measure clinical research study performance across the Network.…”
Section: Implementing and Disseminating Operational Innovationsmentioning
confidence: 99%